Investigating the impact of internal finance, ICG, and CSR on the profitability of Islamic Commercial Banks - Cahya Jati, Farisa Nur; Mohamad Irsyad (JIFA (Journal of Islamic Finance and Accounting), 2024)
Despite the rapid growth of Islamic commercial banks, their Return on Assets (ROA) performance continues to lag significantly behind that of conventional banks, highlighting substantial challenges in enhancing efficiency and profitability. This discrepancy poses a potential threat to their competitiveness in an increasingly saturated banking market. The aim of this study is to assess the impact of internal finance management, the implementation of Islamic Corporate Governance (ICG), and Islamic Corporate Social Responsibility (ICSR) on the profitability of Islamic banks. The research sample comprises 10 Sharia-compliant commercial banks in Indonesia, covering the period from 2015 to 2023, with a total of 90 observations. This study examines the effects of Islamic Corporate Social Responsibility (CSR), Islamic Corporate Governance (ICG), Non-Performing Finance (NPF), Capital Adequacy Ratio (CAR), and Financing to Deposit Ratio (FDR) on the financial performance of Islamic commercial banks. The financial performance is measured using Return on Assets (ROA), while ICG and CSR are assessed through a social disclosure index. The data was analyzed using multiple linear regression in Eviews 10. The hypothesis testing revealed that NPF and ICSR negatively affect financial performance, while CAR, FDR, and ICG had no significant impact.